(untitled) (Progressive Agriculture, 2020)
Soil salinity problem is undoubtedly a major cause which limits the crop production in the coastal region of Bangladesh. Hence an experiment was conducted to observe the stability of cultivars at two coastal saline areas namely Benarpota and Kalapara of Bangladesh based on yield and yield related traits. Eight tomato varieties were used and the experiment was laid out in Randomized Complete Block Design with three replicates. The collected data were analyzed statistically using R-Stat program. The stability of the cultivars was done by R Stat biplot analysis. Yield parameters were significantly affected by salinity at both locations. At Kalapara and Benarpota the variety BARI Tomato-7 gave the highest plant height, 120 cm and 114.67cm, respectively. BARI Tomato-4, BARI Tomato-9 and BARI Tomato-11at Benarpota were earlier for harvest days. The highest number of fruits/plant was recorded from BARI Tomato-11while the lowest number was for BARI Tomato-4 at Benarpota which was statistically similar to BARI Tomato-8 at Kalapara. BARI Tomato-7 gave the highest fruit yield (90.0 t/ha) at Benarpota and (84.67 t/ha) at Kalapara which was significantly different from all other varieties and followed by BARI Tomato-14 (82.67 t/ha) and BARI Tomato-8 (80.33 t/ha). The lowest yield was obtained from BARI Tomato-11 at both the locations. Salt tolerant BARI Tomato-7 was the most suitable variety for Benarpota and Kalapara regions. Based on GGE biplot Genotype (G), Environment (E) and Genotype × Environment (G × E) interactions, BARI tomato-7 and BARI tomato-14 obviously ranked first position at Benarpota and kalapara, respectively. Progressive Agriculture 31 (2): 94-103, 2020